2018
DOI: 10.1111/jre.12534
|View full text |Cite
|
Sign up to set email alerts
|

Clinical concentrations of peroxidases cause dysbiosis in in vitro oral biofilms

Abstract: Commensal species suppress pathobionts by producing H O . Catalase and peroxidases, at clinically relevant concentrations, can neutralize this effect and thereby can contribute to dysbiosis by allowing the outgrowth of pathobionts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…Conversely, elevated concentration of MPO itself can reinforce pathogenic challenge or gingival inflammation. A recent study suggested that high a concentration of MPO can contribute to dysbiosis of the gingival sulcus microbiome [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, elevated concentration of MPO itself can reinforce pathogenic challenge or gingival inflammation. A recent study suggested that high a concentration of MPO can contribute to dysbiosis of the gingival sulcus microbiome [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this system, L-arginine was able to increase the pH of the biofilm, as expected, but it had the added benefit of increasing the production of H 2 O 2 by S. gordonii as well. Conversely, in a 14-species biofilm model containing both H 2 O 2 -producing streptococci and periodontopathogens, the addition of clinically relevant concentrations of the H 2 O 2 -inactivating enzymes myeloperoxidase, lactoperoxidase, and erythrocyte catalase strongly favored the growth of the periodontopathogens at the expense of the commensals 108 . Overall, there is ample clinical and experimental evidence establishing a clear inverse correlation between the abundance of H 2 O 2 produced in an oral biofilm community and the prevalence of pathobionts.…”
Section: Hydrogen Peroxide Production and Biofilm Ecologymentioning
confidence: 97%
“…However, this growth inhibition is counteracted by enzymes that use hydrogen peroxide as substrate, such as myeloperoxidase and catalase, both of which are elevated in the gingival crevicular fluid during periodontitis (myeloperoxidase can be released by neutrophils and catalase from erythrocytes through the action of bacterial hemolysins). 169,170 Peroxidases, therefore, can potentially contribute to dysbiosis (Figure 4).…”
Section: Homeos Tati C Commen Sal S: S Tab Iliz Ation Of He Alth -Cmentioning
confidence: 99%